Development of The Search, Solve, Create, and Share (SSCS) Model with Strengthening Information Literacy for High School Students - Nelita Indah Islami; Andoyo Sastromiharjo; Khaerudin Kurniawan (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to develop the search, Solve, Create, and Share (SSCS) Model with information literacy reinforcement to improve students' ability to write explanatory texts. This study used the research and development with the ADDIE model, which involved Analyze, Design, Develop, Implement, Evaluate. This study employs various data collection techniques, including interviews to understand learning issues, questionnaires to identify student needs and assess product validity, and tests to measure writing skills. The instruments used include observation sheets, questionnaires, interview guidelines, and scoring rubrics, all aimed at supporting the development of the instructional model. The results showed that the SSCS model with information literacy succeeded in improving students' skills that had been tested on 85 students in three high schools in Brebes Regency. The results showed that 16% of students received excellent ratings, 80% of students received good ratings, and 4% received fair ratings. Evaluations from teachers and students indicated positive acceptance of the model, although there were certain aspects which required further adjustments. This study provides a strong foundation for implementing the development of this model in the practice of learning to write explanatory texts in senior high schools.